What are the dietary treatment research priorities for inflammatory bowel disease? A short report based on a priority setting partnership with the James Lind Alliance. Issue 6 (10th August 2017) - Lomer, M. C.; Hart, A. L.; Verjee, A.; Daly, A.; Solomon, J.; Mclaughlin, J.
Abstract: Background: Treatment of inflammatory bowel disease (IBD) involves a multidisciplinary approach comprising medical management and sometimes surgery. Although diet is central to IBD management, the optimal diet for patients with IBD is uncertain. A UK collaborative partnership within the James Lind Alliance was set up between patients, clinicians and other stakeholders to develop research priorities in IBD. The aim of this short report is to provide a comprehensive summary of the research priority findings relating to diet in the treatment of IBD. Methods: The James Lind Alliance Priority Setting Partnership process was used to develop research priorities in IBD. In brief, patients, clinicians and other stakeholders were invited to provide up to five treatment uncertainties in IBD. These uncertainties were collated, revised and ranked, leading to a final top 10 research questions in IBD. Results: A total of 1671 uncertainties from 531 participants were collected and refined to exclude duplicates leaving 1253 uncertainties. Of these, 348 were categorised as diet‐related and grouped according to topic. There were 206 uncertainties related to how diet can be used to treat IBD or alleviate symptoms. Seventy‐two percent of diet‐related questions came from patients. One broadly diet‐related and two diet‐specific treatment uncertainties were included in the top 10 research priorities for IBD. Conclusions: Dietary treatment options in the management of IBD are important research priorities. Almost three‐quarters of diet related questions came from patients, who were particularly interested in how diet can impact disease activity and symptom control.